Selected Social Media as a Digital Platform and its Perceived Value Among Small Businesses - Millecent Marco; Ma. Erika Nisnisan; Fitzgerald J. Perez; Irvin Perono (Journal of Social Entrepreneurship Theory and Practice, 2024)
Small businesses play a crucial role in the global economy, and they often operate with limited resources. Social media can be a game changer, providing a cost-effective way to reach a wider audience. The objective of this study is to establish the most widely used social media in terms of its perceived value.  This study employed quantitative analysis. A self-designed survey questionnaire was used with a Cronbach’s alpha of 0.80. A total of 21 statements were included in the self-made questionnaire on social media factors (cost consumption, brand awareness, attractiveness and accessibility) and perceived value (revenue, customer satisfaction and customer retention). A total of 380 respondents who are small business owners in Metro Manila, Philippines participated in the study and were selected using simple random sampling. Descriptive statistics and Pearson’s chi-square tests were used to establish the results and hypotheses of the study. Among the three social media platforms used, Facebook was the most preferred for its perceived value and effectiveness. Social media use as a digital marketing tool was significantly correlated with perceived value in terms of revenue, customer satisfaction, and customer retention; however, the only meaningful correlation found was between attractiveness and business ownership. The results of this study will help small business operators create marketing strategies to attract more consumers, which will lead to an increase in sales and revenue in the future. In addition, the results can be used as a basis for small businesses to attract more customers by utilizing different social media platforms.